2017
DOI: 10.1590/1518-8345.1638.2894
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded theory study of the intention of nurses to leave the profession

Abstract: Objective: this study explores the process of the development of an intention to leave bedside nursing. Method: the process was studied from the perspective of 21 nurses using the grounded theory method. Data were collected using semi-structured interviews and the constant comparative method of Corbin and Strauss was used for data analysis. Results: according to the participants, the two main categories, "social image of nursing", and "culture and structure of the bedside", were the contextual factors that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 20 publications
1
48
0
3
Order By: Relevance
“…In general such findings are in construct with existing international literature ( 41 ) and it may be explained by the responsibility which can be a stressor and it is increasing along with educational status. Moreover, higher education nurses usually having high expectation for their profession and can feel disappointment when experiencing lack of progress or improvement in the clinical practice ( 42 ). Thus, can lead to the experience of depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In general such findings are in construct with existing international literature ( 41 ) and it may be explained by the responsibility which can be a stressor and it is increasing along with educational status. Moreover, higher education nurses usually having high expectation for their profession and can feel disappointment when experiencing lack of progress or improvement in the clinical practice ( 42 ). Thus, can lead to the experience of depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is not exclusive of Peru. Alilu et al 33 discovered in hospital nurses in Iran that the "social image of nursing" and the "culture and structure of nursing care for bedridden patients" mostly explained the motivation of nurses to abandon the care of hospital patients. Lagerlund et al 34 found in Sweden that about one third of nurses planned to leave their work centers the following year and that this percentage was higher among those who perceived a lack of leadership in the service, no adequate training for cancer patients, and high burnout rates.…”
Section: Professional Discomfort and Stressmentioning
confidence: 99%
“…Em hospitais, é comum a divisão do trabalho ocorrer em forma de turnos, o que permite a prestação de assistência integral e realização de cuidados contínuos, durante as 24 horas do dia (16) . Assim, a maior parte do trabalho de enfermagem é desempenhada durante o dia, uma vez que devem ser evitadas interrupções do sono e repouso do paciente à noite, o que proporciona quantitativo maior de profissionais no turno diurno (2) .…”
Section: Discussionunclassified
“…Durante a história da humanidade, o trabalho sempre emergiu como importante elemento de construção social, permitindo reflexão e reestruturação da identidade e subjetividade das pessoas (1) . Devido aos múltiplos sentidos atribuídos a essa atividade, a relevância deste transcende à esfera individual, em que atua como fonte de renda, autoestima e crescimento pessoal, para representar componente fundamental ao crescimento e desenvolvimento da sociedade (2) .…”
Section: Introductionunclassified
See 1 more Smart Citation